The challenges of teaching, learning and assessment in culinary program via open and distance learning / Norzuwana Sumarjan, Fikri Hanif Muhamad and Ruzaini Ahmad Rashdaini Basha - Sumarjan, Norzuwana; Muhamad, Fikri Hanif; Rashdaini Basha, Ruzaini Ahmad (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The Open and Distance Learning (ODL) mode, encompassing teaching, learning, and assessment processes, has garnered increased acceptance among hospitality educators post-COVID-19. This is attributed to its flexibility, accessibility, and the potential to reach a global audience, offering preparation for unexpected events, such as pandemics. However, ODL implementation is not without challenges. To ensure effective implementation, this study investigates challenges faced by lecturers and students from Kolej Yayasan Pelajaran Johor (KYPJ), aiming to understand pitfalls and propose strategies for smooth implementation. Interviews were conducted with ten students and eight lecturers, and the resulting data were transcribed, coded, and analyzed for themes. A total of twelve themes emerged, with six each from students and lecturers. Common challenges among both groups include internet connections, lack of social interaction and motivation, adaptation to the new learning environment, and disturbances/distractions. Additionally, students face unique challenges related to a lack of practical application and resources, while lecturers grapple with difficulties separating home life and work life, along with health-related anxieties.